Conducting Teacher Stage Coaching Using SAC Media during pandemic Through Techniques - Helwiya Helwiya (Journal of Social Science, 2021)
oaching techniques can be done by the principal to conduct mentoring, mentoring and training on teachers and tendik whose performance is still not in accordance with the standards set. Especially online learning (online) or online learning during the covid-19 pandemic, has a variety of ineffective opportunities. In addition, the problem of utilization of technology and learning media used in the implementation of learning is not maximal. The media used does not support the implementation of the teacher-selected learning model. Improving the competence and skills of teachers in using the media during the pandemic also needs to get the attention of the principal. In the Project to Improve the competence of prospective principals, the author conducts activities to improve the competence of teachers in the implementation of the learning process, especially the use of media through coaching techniques. Based on the results of the study obtained can be concluded that the use of android-based media, one of which is Smart Aplication Creator (SAC), is able to increase the activities of students in following learning from home, which is implemented during the covid-19 pandemic. This can be seen in five aspects, namely based on observation of the implementation of learning, the effectiveness of media use, the results of activities, student achievements and student wellbeing. In the observation aspect of learning implementation there was an increase from 76.50 to 90.39; from the effectiveness aspect of media use increased from 68.33 to 86.11; from the aspect of the evaluation of activities there was an increase from 74.17 to 90.00; from the student achievement aspect increased from 71.94 to 88.89 and from the student wellbeing aspect increased from 81.84 to 85.59.